The Effectiveness of Learning the Indonesian Language Using Spada in the Pandemic Time Covid-19 at Prima Indonesia University Medan - Nova Mawar Hutabarat; Sadieli Telaumbanua (Budapest International Research and Critics University, 2021)
This study aims to find out The Effectiveness of Learning the Indonesian Language Using Spada in the Pandemic Time Covid-19 at Prima Indonesia University Medan. This research is a descriptive qualitative and quantitative descriptive study using online questionnaires and interviews, this is based on the formulation of research problems that require researchers to explore in order to understand and explain what is being studied through an intensive relationship with data sources. Based on the results of questionnaires and interviews and in accordance with the problems, several conclusions can be drawn, namely: 1.Learning Indonesian using SPADA during the Covid-19 pandemic was effective, namely, both from the results of questionnaires and interviews with lecturers and students. 2. The process of learning Indonesian using SPADA starting from planning, implementation and assessment is carried out effectively. 3. The opinion of lecturers and students to make Indonesian language learning more effective using SPADA is to add other features such as Zoom Meeting or Google Classroom.